PENERAPAN METODE CERAMAH DAN SUMBANG SARAN UNTUK PENINGKATAN PRESTASI BELAJAR SEJARAH PADA SISWA SMK NEGERI 2 BUKITTINGGI - Yunita Warmi (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2015)
The purpose of this study is to investigate the effect of using direct instruction and brainstorm strategy in developing student achiement in learning history at SMK N 2 Bukittinggi. This research held in 2 PKAP 2 class. This research used class room action research approach and consists of three cycles. The findings of the study showed that there are significant improvement in student achievement toward three cycles and also the improvement in student activity during the class. Students were involved deeply in learning process and be able to express their opinion about the issues discussed in the class. The researcher recommended the use of this strategy in school as well as conducting more studies regarding its effect by using other samples in different environments.